Accumulation of chemical elements and occurrence of microplastics in small pelagic fish from a neritic environment. (1st January 2022) - da Silva, Joana M.; Alves, Luís M.F.; Laranjeiro, Maria I.; Bessa, Filipa; Silva, Andreia V.; Norte, Ana C.; Lemos, Marco F.L.; Ramos, Jaime A.; Novais, Sara C.; Ceia, Filipe R.
Abstract: The assessment of contaminant exposure in marine organisms often focuses on the most toxic chemical elements from upper trophic level species. Information on mid-trophic level species and particularly on potentially less harmful elements is lacking. Additionally, microplastics have been considered emergent contaminants in aquatic environments which have not been extensively studied in species from mid-trophic levels in food chains. This study aims to contribute to an overall assessment of environmental impacts of such chemicals in a community of small pelagic fish in the North Atlantic. The concentrations of 16 chemical elements, rarely simultaneously quantified (including minerals, trace elements and heavy metals), and the presence of microplastics were analysed in sardines ( Sardina pilchardus ) and mackerels ( Scomber spp. and Trachurus trachurus ) sampled along the Portuguese coast. Biochemical stress assessments and stable isotope analyses were also performed. The chemical element concentrations in S. pilchardus, T. trachurus, and Scomber spp. were relatively low and lower than the levels reported for the same species in the North Atlantic and adjacent areas. No clear relationships were found between chemical elements and oxidative damage in fish. However, the concentration of several chemical elements showed differences among species, being related with the species' habitat use, trophic niches, and specific feeding strategies. The presence of plastic pieces in the stomachs of 29% of the sampled fishes is particularly concerning, as these small pelagic fish from mid-trophic levels compose a significant part of the diet of humans and other top predators. This study highlights the importance of multidisciplinary approaches focusing on the individual, including position data, stable isotopes, and oxidative stress biomarkers as complementary tools in contamination assessment of the marine mid-trophic levels in food chains. Graphical abstract: Image 1 Highlights: All 16 chemical elements analysed presented low concentrations in fish muscle. No relationships between oxidative stress and element concentrations were found. The variation in elements was related with habitat use and feeding strategies. Microplastics were found in 29% of sampled fish (1.13 ± 0.35 per contaminated fish). Sardines presented larger plastic pieces when compared to mackerel species.